Relationship of Parental Discipline, Intensity of Peer Group Communication, and Suitability of The Election Department, on FISIP Undip Student Achievement - Yoga Aprillianno .; Drs. Hj. Sri Widowati Herieningsih, MS (Interaksi Online, 2016)
The purpose of this study was to determine the effect of parental discipline, the intensity of communication in the peer group, and the suitability of the election department, on FISIP Undip student achievement. The theory of reasoned action, theory of reference groups and problematic integration theory is used to explain the relationship of parental discipline, intensity of communication within the peer group, and the suitability of the election department, on FISIP Undip student achievement. The population used was a 90 students S1 FISIP Undip, with a random cluster sampling technique. Pearson correlation analysis is used to test the hypothesis. Hypothesis test showed the value of variable significance of parental discipline of 0.294, the significant value of the variable intensity of communication in the peer group for 0.977, and the value of variable significance suitability election majors of 0.077, or all of the significant value smaller than α (0.05), so all the variables do not affect the variable FISIP Undip students achievement. The study then provide advice to the parents of students and groups of friends of students to be able to further improve and provide motivation to get better learning achievement.